Regional monograph : intraregional and extraregional mobility the new Caribbean migration - Mills, Frank L. (CARICOM Secretariat GeorgetownGY, 1997)
Focuses on the mobility of migrants within the Caribbean - primarily within the CARICOM - Caribbean Common Market - countries. Looks also at emigrants from these countries, with particular attention to a select set of characteristics of emigrants from CARICOM countries to the United States.